EFFECTS OF BRAIN AGE TO INCREASE COGNITIVE FUNCTION IN ELDERLY - Agoes, Achdiat; Lestari, Retno; Alfaruqi, Saifullah (Malang Neurology Journal, 2016)
Background. The concept of cognitive (from Latin cognosere, to know or to recognize) refers to the ability to process information, applying knowledge, and change the trend. cognitive function of the elderly can be optimized through a variety of ways, one of that way is the brain training game (Brain Age). The game was created specifically to train the cognitive function of elderly.Objective. To determine the effect of Brain Ag) to the improvement of cognitive function in the elderly in Malang. Methods. Quasi-experimental pretest-posttest approach, the treatment and control groups, and the sampling is done with purposive sampling to obtain the 20 respondents. Data collection instrument in this study are in general cognitive tests by using a measuring instrument MMSE. Then the data were analyzed by Mann-Whitney test showed p value 0.000 <Î± 0.05. Results. There is the effect of therapy brain training game (Brain Age) on increasing cognitive function of elderly in Malang.Conclusion. Therapy of brain training game (Brain Age) can be used as an alternative method of nursing actions that can be implemented in nursing geriatric and to consider inter-community cooperation between the elderly or nursing home.